Optimalisasi Kewenangan Majelis Permusyawaratan Rakyat (MPR) Dalam Sistem Ketatanegaraan Indonesia - Anggraini, Raden Roro Evitasari Yurika; Wasti, Ryan Muthiara (UI Scholars Hub, 2022)
In the Indonesian constitutional system, it is very influential on changes to the amendments UUD 1945 which in these changes to state institutions of course experience differences in authority from before the amendment and after the amendment. Regarding these changes, MPR may experience many changes in it regarding the position and authority in the Indonesian state administration. The MPR is no longer the highest state institution as before the amendment, which is now in parallel with other institutions. So in the Indonesian state administration, there are no higher state institutions between one another. With this change, the MPR's authority has been reduced, which of course has various impacts on the Indonesian state administration system. The MPR's equal position with others is also a form of checks and balances between other institutions.